Radiation-induced eCIRP causes macrophage phagocytic dysfunction via mitochondrial impairment and ferroptosis - Zhou, Mian; Ma, Gaifeng; Li, Jingsong; Yamaga, Satoshi; Brenner, Max; Aziz, Monowar; Wang, Ping (Frontiers in Immunology, 2025)
Ionizing radiation causes immune dysfunction, increasing susceptibility to infection and mortality. Extracellular cold-inducible RNA-binding protein (eCIRP) is released from cells during irradiation. This study investigates how radiation-induced eCIRP release causes macrophage phagocytic dysfunction via ferroptosis, with a focus on the role of mitochondrial dysfunction. Peritoneal macrophages were exposed to 10-Gy irradiation. eCIRP levels in the culture supernatants were assessed post-irradiation by ELISA. Ferroptosis was assessed by measuring lipid peroxidation and glutathione peroxidase 4 (GPX4) expression. Mitochondrial function was assessed using Mito stress assay in a Seahorse metabolic analyzer. Phagocytic activity was quantified by measuring the uptake of pHrodo-labeled E. coli. Our results demonstrated that 10-Gy irradiation induced ferroptosis in peritoneal macrophages. Markers of ferroptosis, lipid peroxidation, were significantly elevated, and GPX4 was significantly downregulated in a time-dependent manner on days 3 and 5 post-irradiation. We unveiled a strong time-dependent correlation between post-irradiation eCIRP release and the increases in ferroptosis and macrophage phagocytic dysfunction at days 3 and 5. Furthermore, radiation-induced eCIRP positively correlated with mitochondrial dysfunction, evidenced by marked reductions in basal and maximal respiration and ATP production, mirroring effects of direct eCIRP treatment. Crucially, the application of MFG-E8-derived oligopeptide 3 (MOP3), a novel opsonic eCIRP inhibitor, effectively cleared eCIRP, restoring mitochondrial function, reducing ferroptosis, and improving phagocytosis in irradiated macrophages. These findings establish that radiation-induced eCIRP release drives mitochondrial dysfunction and ferroptosis, thereby impairing macrophage phagocytosis. Targeting eCIRP offers a promising therapeutic strategy to enhance host defense following radiation exposure.